SISTEM INFORMASI GEOGRAFIS BERBASIS WEB PEMETAAN LOKASI DOKTER SPESIALIS KOTA BANDA ACEH - Prasetya Wardana; Anggi Juliansa (Ubudiyah Indonesia University, 2020)
The city of Banda Aceh, which is a population with a variety of Acehnese races and different backgrounds, is caused byurbanization where many people are still groping in obtaining information related to the location of the presence of apracticing specialist or in the hope that every complaint can be handled promptly and efficiently. with respect to time todirectly track information by the sufferer, besides that it can also find out what hours and days a specialist doctor is inthe location of a practice other than at the Hospital. The current phenomenon of various diseases and suffered fromchildren to adulthood and even old age as if they knew no age which resulted in sufferers flocking to go to treatmentboth inside and outside the country even to get a doctor who is an expert or specialist in accordance with the di seasesuffered with hope for healing. Therefore it is very necessary for a Geographic Information System application to trackthe whereabouts of specialists to help patients who seek treatment, where only interact with this application can find thelocation of a specialist doctor who is searched according to the disease suffered by the patient. Departing from thisproblem the author wants to make a Web-based Geographic Information System Mapping the Location of the SpecialistCity of Banda Aceh. Data sourced from the Banda Aceh City Health Office. The system is able to provide Web-basedGeographical Information Mapping to the Location of Specialist Doctors in the City of Banda Aceh, this can be seen inthe application displayed through the Geographic Information System. The system can be used to see the distribution ofSpecialist Doctors with a record of all inputted data in the City of Banda Aceh. The results presented by the system canbe used as a means to find out the location of distribution of Specialist Doctors in Banda Aceh City with variousspecializations